Are heart transplant recipients more at risk for anal squamous carcinoma than other solid organ transplant recipients?. Issue 1 (26th March 2022) - Roelandt, Philip; Droogne, Walter; Vörös, Gábor; Van Aelst, Lucas; Rega, Filip; van Cleemput, Johan
Abstract :